2021
DOI: 10.3389/fsufs.2021.550821
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and Common Ground in Wild and Domestic Fine Fiber Production in Argentina

Abstract: This work analyzes possible obstacles to developing new products or old merchandise using an innovative method. It will look into stakeholders of fine fiber and meat products from three distinctive socioecological systems. Through three case studies, we explore how natural resources management is connected to interests, values, and knowledge by stakeholders, which include government, the scientific community, and people with rural livelihoods. The government vertex is the national and provincial authorities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(57 reference statements)
0
3
0
1
Order By: Relevance
“…Initially, VICAM researchers developed a top-down experience. The project emphasized teaching adequate procedures to private producers of the Puna, belonging to an Association Cieneguillas (2003)(2004)(2005) and Santa Catalina Cooperative (2012, 2014) (Bonacic and Gimpel, 2003;Vilá et al, 2010). Initially the project and later reports showed that the conceptual framework was conceived as a top-down experience.…”
Section: A Commentary Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, VICAM researchers developed a top-down experience. The project emphasized teaching adequate procedures to private producers of the Puna, belonging to an Association Cieneguillas (2003)(2004)(2005) and Santa Catalina Cooperative (2012, 2014) (Bonacic and Gimpel, 2003;Vilá et al, 2010). Initially the project and later reports showed that the conceptual framework was conceived as a top-down experience.…”
Section: A Commentary Onmentioning
confidence: 99%
“…com/watch?v=L_A_rnEgHzo&t=86s) (2014) presented. Detailed descriptions of these experiences have been published (Vilá et al, 2010(Vilá et al, , 2020aArzamendia et al, 2014;Vilá and Arzamendia, 2020).…”
Section: A Commentary Onmentioning
confidence: 99%
“…1-27 2015; Horning, Bauer, & Cohen, 2016). De manera complementaria, algunos trabajos centrados en el estudio de los SES aplican el concepto de red desde una visión cualitativa o como metáfora de una estructura reticular, pero no emplean el ARS y su base matemática (Lavorel et.al., 2019;Von Thungen, Martin & Lanari, 2021).…”
Section: Introductionunclassified
“…This bias also resulted in pastoral system being seen as a threat to environmental sustainability, especially when analysed with the methods and assumptions used to assess intensive or industrial livestock systems (e.g., Lebacq et al, 2013). There is evidence to suggest that pastoral systems generate both ecosystem services and disservices, hence the trade-offs between them need to be embraced to inform development strategies and policies (e.g., Von Thungen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%